2014
DOI: 10.1108/ijlss-02-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

The application of Lean Six Sigma to the configuration control in Intel’s manufacturing R&D environment

Abstract: Purpose-The purpose of this paper is to provide an example of Lean Six Sigma (LSS) application in research and development (R&D) organizations to eliminate waste and improve systems based on available data that in turn improves the innovative environment. Manufacturing R&D involves designing and testing innovative concepts and taking them into high-volume manufacturing. The infrastructure associated with such organizations involves experimental manufacturing lines with the ability to evaluate the result under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 14 publications
1
23
0
1
Order By: Relevance
“…Lean Six Sigma is gaining a lot of popularity. This is evident from a number of publications on this topic (Cabrita et al 2015;Panat et al, 2014;Snee, 2010). Snee (2010) shows how Lean Six Sigma can be used to support finances during economic downturns.…”
Section: Lean Six Sigma's Impact Of Resourcesmentioning
confidence: 96%
“…Lean Six Sigma is gaining a lot of popularity. This is evident from a number of publications on this topic (Cabrita et al 2015;Panat et al, 2014;Snee, 2010). Snee (2010) shows how Lean Six Sigma can be used to support finances during economic downturns.…”
Section: Lean Six Sigma's Impact Of Resourcesmentioning
confidence: 96%
“…Al et al [6] developed a model using lean to map and improve the functions of R&D project activities. Foruhi et al [10] identified and determined the customer value as the main focus of lean concepts and how can be applied to all disciplines including R&D. Hence, Panat et al [20], through a case study, demonstrated the benefits of using lean combined with Six Sigma methodology in the infrastructure and operations of the R&D organisation.…”
Section: Lean In Project-based Organisations/randdmentioning
confidence: 99%
“…Figure 1 shows the generic representation methodology or a project where there is an input (e.g., requirements, statements) provided by a stakeholder (e.g., supplier, customer), where there is a process to deliver an output [13]. In Lean Six Sigma, there is a similar mapping of a flow process known as SIPOC (supplier, input, process, output, customer) [20]. This diagram also works as a guide to identify metrics as KPIs.…”
Section: Measure and Analyse Phasementioning
confidence: 99%
“…They propose a model to identify the critical factors in the health sector, through the construction and validation of an instrument that will yield the results to be analyzed to determine the significant critical factors [42]. Panat, Dimitrova, Selvy Selvamuniandy, Ishiko and Sun research have as an objective to develop LSS in research and development organizations, aiming to eliminate waste and improve the systems based in the available data and at the same time would improve the innovative environment [43].…”
Section: Health Research and Developmentmentioning
confidence: 99%